PENGARUH WORD OF MOUNTH DAN PRODUCT QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA KEJU KESU - Amri; Yayuk Yuliana; Harahap, M. Guffar (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2022)
This study aims to determine the effect of Word of Mount and Product Quality on purchasing decisions on Kesu Garu Cheese II Medan. The population in this study were consumers at Kesu Garu II Cheese Medan on average as many as 38 customers per day, so that there were 266 consumers at Kesu Garu II Medan Cheese Outlet for one week. The number of samples to be taken in this study is 73 samples. The method used by the researcher is a descriptive method through a quantitative approach. The data collection used is by using a questionnaire given to respondents. The data is processed using SPSS 20.0 for windows.. The partial test results show that the tcount value of the Word Of Mouth variable (X1) is (4.097) greater than the ttable value (1.994). So in this case partially that the Word Of Mouth variable affects the Purchase Decision on Kesu Garu Cheese II Medan. The partial test results show that the tcount value of the Product Quality variable (X2) is (3.051) greater than the ttable value (1.994). So in this case partially that the Product Quality variable has an effect on the Purchase Decision on Kesu Garu II Cheese Medan. The results of the F-test that the independent variables (X1 and X2) in the form of Word Of Mouth and Product Quality simultaneously affect the dependent variable (Y) Purchase Decision on Kesu Garu Cheese II Medan and the effect is positive with a significant level (α) of 5%. With the results of the acquisition of Fcount> Ftable which is 67.574> 3.13 and by looking at the probability (sig) which is smaller than the significant level (0.000 <0.05), it can be concluded that the equation model is accepted and has a significant effect. The coefficient of determination is 0.649 ( 64.9%). So it can be said that 64.9% of the variation in the dependent variable, namely the Purchase Decision of Kesu Garu II Medan Cheese in the model can explain the Purchasing Decision variable of Medan's Kesu Garu II Cheese, while the remaining 35.1% is influenced by other variables outside the model.